A teleost hepcidin derived peptide mSshep 2: Protection against Edwardsiella piscicida infection via preservation of intestinal integrity, modulation of immune responses, and regulation of gut microbiota - Hao Jing; Guang-hua Wang; Zhi-shu Zhu; Nuo Sun; Kai Yang; Zi-yue Chen; Yi-lin Du; Zi-qi Wang; Min Zhang (Aquaculture, 2027)

Bioaccumulation, oxidative stress, immune disruption, and metabolic alterations in Mytilus galloprovincialis exposed to nano-copper oxide - Yitong Gong; Yang Lin; Ziyan Lang; Jiawan Lv; Jing Sun; Liming Wang; Shujun Li; Weiang Zhang; Xiaoli Liu; Liping You (Marine Pollution Bulletin, 2026)

Accelerating Li+ recovery kinetics of 5TiO2·2H2O adsorbents from original geothermal water by configuring TiO2·H2O phase - Lin Jing; Chunxi Hai; Xuemei Zuo; Lijuan Zhang; Shengde Dong; Yanxia Sun; Luxiang Ma; Qi Xu; Xin He; Yuan Zhou (Desalination, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Genetic ancestry of the Mulam ethnic group: admixture from ancient Yellow River, southern native, and Austronesian populations - Wendi Dang; Xiaoming Wu; Jing Zhao; Song Lin; Xirui Wang; Xiaomin Yang; Jin Sun; Tielin Yang; Chuan-Chao Wang; Hu-Qin Zhang (Human Genetics, 2026)

DLEU2 promotes the migration and invasion of papillary thyroid carcinoma cells through the ELAVL1/RCC2 axis - Suwei Zuo; Sinuo Sun; Yuanyuan Wang; Jiayin Song; Yanmeng Zhou; Shibo Liu; Gang Xue; Xu Lin; Jing-fang Wu (Functional & Integrative Genomics, 2026)

Rhamnogalacturonan I in commercial samples of polygalacturonic acid is a functional driver: A study of isolation, structural elucidation, role in immunostimulation and hydrogel mechanics - Xueting Zhang; Chuying Huo; Pengfei Shan; Niping Chen; Quanwei Zhang; Hauyee Fung; Wenting Zhao; Jing Li; Peili Zhu; Shanlong Tang; Ye Yuan; Lin Sun; et al. (Food Hydrocolloids, 2026)

A TFPI-1 homolog from Sebastes schlegelii: Characterization of C-terminal endogenous cleavage and antimicrobial role of derived peptide - Zhi-Shu Zhu; Zi-Yue Chen; Guang-Hua Wang; Hao Jing; Kai Yang; Nuo Sun; Yi-Lin Du; Zi-Qi Wang; Min Zhang (Fish & Shellfish Immunology, 2026)

Temporal sulfur redox reprogramming enables control-oriented intensification of sulfur-based autotrophic denitrification - Kun Zheng; Han-Bing Xiao; Yi-Lu Sun; Zhou-Yang Li; Jing-Zhe Zhang; Han-Lin Wang; Ai-Jie Wang; Xue-Ning Zhang (Water Research, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Ru-Co bimetallic catalysts with synergistic crystalline phase regulation and hydrogen spillover for deep hydrodeoxygenation of lignin oil - Jing-jing Wu; Jia-yuan Tian; Feng Lin; Yu-long Ma; Yong-gang Sun; Pei Ma; Shuai-lei Li; Xue Zhang; Yi-shu Ma; Xiao-lin Xue (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Interspecies interactions in dual-species biofilms formed by Staphylococcus aureus and Candida albicans: Phenotypic and transcriptomic insights - Jing Dong; Lin Zhu; Xin Tian; Mandlaa; Ziyu Sun; Zhongjun Chen (Food Research International, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Hepatic immunometabolic reprogramming of Sebastes schlegelii in response to Photobacterium damselae subsp. piscicida infection: biochemical, transcriptomic and metabolomic analyses - Hao Jing; Guang-hua Wang; Kai Yang; Zi-yue Chen; Zhi-shu Zhu; Nuo Sun; Yi-lin Du; Zi-qi Wang; Min Zhang (Fish & Shellfish Immunology, 2026)

Toxic effects of acute atrazine exposure on the physiological functions and transcriptional levels in non-targeted marine invertebrates (Chlamys nobilis) - Jing Sun; Beiyu Yan; Yaoting Liu; Qing Lin; Weili Wang; Hongkuan Zhang; Huaiping Zheng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A Pt/h-Co-Nc nanozyme hydrogel air-fuel cell mediating cascade DNA walking for point-of-care detection - Ning Li; Lin Sun; Kaili Wang; Lihui Mao; Xuecai Tan; Haibo Wang; Ke-Jing Huang; Shaogang Liu (Chemical Engineering Journal, 2026)

Construction of low-pressure separation membranes with hierarchically porous structure via cross-linked cyclodextrin polymer modification for efficient dye/salt separation - Jing Yang; Xinyang Li; Zining Guo; Ligang Lin; Wensong Ma; Huiyang Shang; Yue Sun; Mengzhuo Zhang; Hao Wu; Qi Wang; Mengfan Hou; Hongchao Li (Chemical Engineering Journal, 2026)

Hydraulic conductivity and the associated xylem anatomy as reliable predictors of tree productivity for Populus species along the fast-slow spectrum - Attaullah Khan; Xue-Wei Gong; Jing-Jing Guo; Cheng-Lin Yuan; Shen-Hao Song; Zhong-Yi Pang; Yan-Hui Peng; Xue-Kai Sun; Guang-You Hao (Agricultural and Forest Meteorology, 2026)

Species Diversity, Parasitism Rates, Longevity, and Population Dynamics of the Parasitoid Complex Attacking Ophelimus bipolaris in China - Jin Hu; Yuan-Hao Li; Jing-Hui Su; Jin-Bo Sun; Guo-Bao Qin; Yan Qin; Lai-Feng Luo; Lin-Xia Feng; Kai-Jian Han; Zoya Yefremova; Jun Li; Xia-Lin Zheng (Neotropical Entomology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

BR signaling mitigates Cu toxicity in rice by integrating ROS homeostasis with copper translocation - Huaying Du; Lulu Sun; Quanlei Shentu; Jinglin Pan; Jing Bi; Zishen Liao; Xianhui Lin; Dongmei Chen; Rensen Zeng; Yuanyuan Song (Plant Science, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Revealing the mechanism of ordered two dimensional Co3S4 composite anode electro-enhanced peroxymonosulfate activation and singlet oxygen production - Chengkai Mao; Manchen Lin; Weixiong Jian; Jing Sun; Yutong Cui; Jingming Wen; Haiyang Shao; Minghong Wu (Journal of Environmental Chemical Engineering, 2026)

Potent sucrase inhibition by purple sweet potato anthocyanins for glycemic control: unveiling peonidin-3-caffeoyl-feruloylsophoroside-5-glucoside as the key functional monomer and its interaction mechanism - Jing Li; Yushan Wang; Luyao Wang; Zhenfeng Yue; Binqiao Sun; Siqi Lin; Si Li; Guiyun Chen; Luelue Huang (Food Chemistry, 2026)

Structural modifications triggered by environmental stress improve bioactivities of exopolysaccharide from endophytic bacterium Methylorubrum sp. Y19 of Taxus cuspidata - Junbo Liang; Xiaohan Zhang; Lin Zhu; Jing Luan; Keyu Sun; Jing Wang; Shuhong Ye (Food Bioscience, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Corrigendum to ’Effects of perfluorononanoic acid (PFNA) on membrane system, physiological and metabolic activities in Microcystis aeruginosa’ [Journal of Environmental Sciences 165 (2026) 703–714] - Jintong Sun; Liang Wu; Chenglian Feng; Haizhuan Lin; Jing Ye (Journal of Environmental Sciences, 2026)

Effects of perfluorononanoic acid on membrane system, physiological and metabolic activities in Microcystis aeruginosa - Jintong Sun; Liang Wu; Chenglian Feng; Haizhuan Lin; Jing Ye (Journal of Environmental Sciences, 2026)

Injectable icaritin-loaded Pickering emulsion gel for overcoming immunotherapy resistance in malignant ascites - Huijuan Wei; Jing Wang; Lin Zhong; Jia Zhang; Xuqi Sun; Xuanwen Bao; Haibo Zhang; Dong Chen; Jianhao Liu; Xiaomeng Dai; Peng Zhao (Chemical Engineering Journal, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Novel insights into the effects of co-heat treatment versus pre-heat on the interaction between rice glutelin and aroma compounds - Lin Zhu; Mengke Zheng; Jing Li; Zhaodong Zhu; Shihao Sun; Donghao Zhang; Jihong Wu (Food Hydrocolloids, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Anti-leukemia steroidal saponins from Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Zhang; Yu-Chen Fan; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Yi-Lin Liu; Yi-Bo Shen; Chao Liu; Jin-Yue Sun; Jin-Zhong Hu; et al. (Phytochemistry, 2026)

Construction of PtRu/Nb2O5 catalysts with high performance and good water- and chlorine-tolerance for the synergistic oxidative removal of multi-component VOCs - Meiyue Li; Qinpei Sun; Yiwen Jia; Jiguang Deng; Zhiquan Hou; Lu Wei; Zhen Wei; Lin Jing; Liangshi Wang; Yuxi Liu; Hongxing Dai (Journal of Environmental Sciences, 2026)

Germinated quinoa flour as a functional ingredient in wheat bread: Impact on dough microstructure, rheology, and nutritional-sensory profile - Yanan He; Yaxuan He; Jiayin Huang; Huan Sun; Lin Cheng; Jing Zhang; Jun Liu; Haijie Liu (Food Hydrocolloids, 2026)

Probiotics as a Therapeutic Strategy for Obesity: New Thoughts on the Stress Response Mechanisms of Probiotics In Vitro and In Vivo - Dingkang Wang; Chao Li; Jingru Ma; Ruijie Xu; Wei Jing; Sha Liu; Xiaomin Sun; Lin Shi; Youfa Wang (Probiotics and Antimicrobial Proteins, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Hydraulic optimization of a V-weir-orifice composite fishway with column structures of different shapes for estuarine connectivity restoration - Chunying Shen; Jinghan Lin; Mingming Wang; Yubin Chen; You Wang; Jing Sun (Ocean Engineering, 2026)

Antimicrobial peptide mSshep 1 from Sebastes schlegelii combines broad-spectrum antibacterial activity, membrane-disruptive mechanism and in vivo protective efficacy - Hao Jing; Guang-hua Wang; Kai Yang; Zi-yue Chen; Zhi-shu Zhu; Nuo Sun; Yi-lin Du; Zi-qi Wang; Min Zhang (Fish & Shellfish Immunology, 2026)

Effect of perovskite A-site disorder on its activity in solid-state CO2 electrolysis - Shuo Liu; Lin-Bo Liu; Biao Ouyang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Jing-Li Luo; Subiao Liu (Chemical Engineering Journal, 2026)

Ferrihydrite accelerates carbon turnover by regulating interspecific electron transfer in petroleum-contaminated soil - Xin Yu; Yuewei Yang; Jialu Sun; Pengju Zhong; Xiaolin Zhang; Jing He; Zhiwen Lin; Dejun Wang; Wenqing He; Xiaojing Li (Chemical Engineering Journal, 2026)

AeroTrans: Hourly AOD retrieval over land from MSG-1/SEVIRI imagery integrating Transformer and transfer learning - Yulong Fan; Zhanqing Li; Lin Sun; Oleg Dubovik; Zhihui Wang; Fan Cheng; Xiaohang Shi; Jing Wei (Remote Sensing of Environment, 2026)

Enhancing cloud detection across multiple satellite sensors using a combined Swin Transformer and UPerNet deep learning model - Shulin Pang; Zhanqing Li; Lin Sun; Biao Cao; Zhihui Wang; Xinyuan Xi; Xiaohang Shi; Jing Xu; Jing Wei (Remote Sensing of Environment, 2026)

Three-dimensional numerical investigation of vortex-induced motion of low aspect ratio cylinders - Jin Miao; Hongyuan Sun; Haihua Lin; Dexin Liu; Shuo Ren; Kefeng Yan; Jing Xu (Ocean Engineering, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Study on the structure-activity relationship and effect evaluation of benzo -γ -pyrones anti-S. aureus Hla inhibitors - Tingting Sun; Lin Jiang; Lijiao Yang; Siyi Chen; Yang Liu; Jing Liu; Fei Xu (Food Bioscience, 2026)

Epidemiological characteristics of Chlamydial infection in hospitalized children in China: A nationwide retrospective study - Huiwen Zheng; Xinyu Wang; Xirong Wu; Yajie Guo; Feina Li; Jing Xiao; Hui Qi; Weiwei Jiao; Guoshuang Feng; Ju Yin; Lin Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

Diurnal double-pulse of nitrate dynamics in Mount Qomolangma glacial runoff - Dandan Yang; Lin Li; Tandong Yao; Baiqing Xu; Jing Gao; He Sun; Dongmei Qu (Science Bulletin, 2026)

Topography and rural settlement control the evolution of sloping cropland toward diversity—evidence from the Three Gorges Reservoir Area over half a century - Xinyi Sun; Wenxin Zhao; Yangbing Li; Ying Huang; Lin Liu; Jing'an Shao (Journal of Cleaner Production, 2026)

Autonomous DNA walker-driven bioelectrocatalytic system with spatiotemporal control for ultrasensitive molecular diagnostics - Bei Zhang; DanYao Tang; Lin Sun; Haibo Wang; Jiawen Wu; Yanni Luo; Ke-Jing Huang; Shengyu Xie (Journal of Environmental Chemical Engineering, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Cadzow Filtering Method Based on Adaptive Singular Value Decomposition - Zhong-lin Cao; Dan Wang; Peng-yuan Sun; Le Li; Ding-yu Xiong; Wen Yang; Yin-yu Wen; Jing Bai (Applied Geophysics, 2026)

Natronorubrum marinum sp. nov., Natronorubrum amylolyticum sp. nov., Natronorubrum halobium sp. nov., and Natronorubrum salinum sp. nov., halophilic archaea from a coastal saline-alkali land and two saline lakes - Ya-Ling Mao; Yao Hu; Zhang-Ping Wu; Ya-Ping Sun; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Electrode Net: tailoring deep learning with signed distance field for fast and accurate multiscale design of porous electrodes - Pengzhu Lin; Jing Sun; Yinglun Tang; Jiayou Ren; Xiaosa Xu; Jin Li; Changxiang He; Shuaibin Wan; Wenjia Li; Tianshou Zhao (Science Bulletin, 2026)

Modulation of viscosity, swallowability, and stability of starch-based thickener: The effect of konjac gum and xanthan gum - Haoran Fan; Lin Sun; Xiaodan Liu; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Characteristics of benthic microeukaryotic communities in different ecosystems of the Yellow River Estuary salt marshes - Jing Han; Lin Sun; Junrong Liang; Yahui Gao; Changping Chen (Estuarine, Coastal and Shelf Science, 2026)

Enhancement of anaerobic digestion performance of waste activated sludge by sludge-derived alkaline-slow-release mesoporous biochar: Insights into electron transfer, extracellular polymeric substances, and microbial metabolism - Wei Wu; Jing Sun; Qian Ping; Lin Wang; Yongmei Li (Chemical Engineering Journal, 2026)

Nanoformulated resveratrol enhanced the treatment of atherosclerosis - Cai Cheng; Yan Lin; Xin Chen; Yang Xie; Xing Jiang; Jinting Chen; Yanling Wu; Zaiyi Luo; Jiayi Xu; Zhirong Zhang; Changguang Wang; Pei Jing; et al. (Chemical Engineering Journal, 2026)

The p -JNKThr183/Tyr185 / p -Keap1Thr43 /Keap1 axis mediates arsenic-induced endothelial dysfunction by coordinating Chaperone-mediated autophagy with macroautophagy - Jinyu Li; Jin Cheng; Zhihan Yang; Lin Gao; Qiaoling Liu; Jing He; Yishan Dong; Shuo Wang; Jing Cui; Ziqi Xu; Dianjun Sun; Wei Zhang (Chemico-Biological Interactions, 2026)

Lactobacillus johnsonii JJB3 Ameliorates Oxidative Stress-Induced Intestinal Injury and Mitochondrial Damage by Promoting BNIP3L-Mediated Mitophagy - Xingmei Liu; Jinge Xin; Ning Sun; Yuhua Qin; Haonan Huang; Benhao Chen; Lixiao Duan; Yanxi Zhou; Dandan Wang; Bo Jing; Yan Zeng; Dong Zeng; et al. (Probiotics and Antimicrobial Proteins, 2026)

Microalgae-derived biodiesel: Review on microalgae species, genetic modification, cultivation strategies, and mutagenesis - Jing Tian; Jianqun Lin; Guoqiang Zhuang; Peiyao Sun; Pengxue Geng; Linxu Chen; Xianke Chen (Algal Research, 2026)

A physically-refined regional climate model for the Tibetan Plateau - Kun Yang; Xu Zhou; Xiaogang Ma; Deliang Chen; Fahu Chen; Yongjiu Dai; Yaozhi Jiang; Anning Huang; Yanluan Lin; Jiarui Liu; Hui Lu; Jing Sun; et al. (Science Bulletin, 2025)

Rising river habitat risk in China is driven by climate change and intensive human activities - Xuewei Wang; Jing Wang; Chunye Lin; Jingjing Liu; Nuo Cheng; Guoqiang Qiu; Guangru Sun (Journal of Environmental Management, 2025)

Effects of ultrasound-assisted extraction on the structural and functional properties of dietary Fiber from mulberry - Bin Chen; Xiaolin Liu; Xuzhen Guo; Lu Tang; Guiying Su; Zhuoyuan Lin; Jing Sun; Bo Wang; Lei Tao; Fengzhong Wang (Food Chemistry, 2025)

Biocatalytic synthesis of margarine fat with zero-trans and low saturated fatty acids by Pichia pastoris lipase immobilized on resin - Xiao-Ya Guan; Jing Zhang; Xiao-Wei Chen; Lin-Shang Zhang; Shang-De Sun (Food Chemistry, 2025)

Ultra-stable Pd/NaInY catalyst with atom-dispersed indium modification of NaY zeolite for CO direct esterification to dimethyl carbonate - Yi-Jing Feng; Xiao-Yuan Tan; Jian Lin; Wen-Qiang Zou; Jing Sun; Zhong-Ning Xu; Guo-Cong Guo (Chemical Engineering Journal, 2025)

Micellar co-delivery of ibuprofen and zonisamide selectively to inflamed tissue following spinal cord injury - Shuzao Wang; Yan Lin; Zhenzhen He; Zaiyi Luo; Yanling Wu; Yan Wang; Xing Jiang; Jinting Chen; Jili Wu; Xingyue Zhong; Zhirong Zhang; Changguang Wang; et al. (Chemical Engineering Journal, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Unraveling the potential mechanism and prognostic value of pentose phosphate pathway in hepatocellular carcinoma: a comprehensive analysis integrating bulk transcriptomics and single-cell sequencing data - Bin Li; Tao Zeng; Cui Chen; Yuankai Wu; Shuying Huang; Jing Deng; Jiahui Pang; Xiang Cai; Yuxi Lin; Yina Sun; Yutian Chong; Xinhua Li; et al. (Functional & Integrative Genomics, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Unveiling diurnal aerosol layer height variability from space using deep learning - Yulong Fan; Lin Sun; Zhihui Wang; Shulin Pang; Jing Wei (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Low-dose fluoride exposure disrupts CD4+ T cell balance in humans and rats - Jing Zhou; Siqi Zhu; Yiyi Zhang; Fengyu Xie; Bingshu Liu; Lin Yuan; Xiaona Liu; Dianjun Sun; Wei Wei (Environmental Research, 2025)

Regulating the charge transport ability of the TiO2/CsPbI2Br perovskite interface layer by MoS2 nanoparticles for high-performance carbon-based all-inorganic perovskite solar cells - Zhaowei Huang; Lin Gao; Fengli Liu; Shihui Xu; Yaxuan Chai; Jing Li; Qing Yao; Haozhen Deng; Liuxue Sun; Jihuai Wu; Zhang Lan (Chemical Engineering Journal, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

Candidate pathway for low-carbon methanol production from coke oven gas and biogas: A multi-dimensional techno-economic and environmental analysis - He Zhu; Yutong Lin; Jing Tian; Zhichao Li; Yidan Zhang; Shuqing Li; Yuhan Sun; Jun Zhang (Chemical Engineering Journal, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

An activatable aptamer probe Q2c for detection of grouper iridovirus - Mingzhu Liu; Jing Huang; Lin Huang; Qiwei Qin; Yanlei Chang; Lei Shi; Yun Sun; Yongcan Zhou; Shaowen Wang; Shuyu Han; Qing Yu; Pengfei Li (Aquaculture, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

Rapid detection of duck egg ovalbumin (D-OVA) in surimi via fluorescent immunochromatographic assay utilizing shark-derived single-domain antibody - Zhong-Lin Li; Ling-Jing Zhang; Kai-Yuan Cao; Jian-Lian Huang; Chang-Gong Zhang; Le-Chang Sun; Yu-Lei Chen; Min-Jie Cao (Food Chemistry, 2025)

A small amount of Pd promotes CO2 adsorption and reduces carbon deposition to double the stability of NiFePd/MgAlO catalyst for plasma-assisted dry reforming reaction - Lian-He Zhao; Shu-Juan Lin; Jian-Feng Diao; Ming-Sheng Wang; Jing Sun; Zhong-Ning Xu; Guo-Cong Guo (Chemical Engineering Journal, 2025)

Enzymatic resistance of starch-polyphenol inclusion complexes: polyphenol inhibition and structural changes during in vitro digestion - Haoran Fan; Lin Sun; Xu Yao; Yangyang Wen; Xuesong Xiang; Hongyan Li; Jing Wang; Baoguo Sun (Carbohydrate Polymers, 2025)

Low-intensity pulsed ultrasound enhances delivery of 30 nm Q10 for improving mental and memory disorder in APP/PS1 mice - Qi Luo; Xuanjie Ye; Jinan Xu; Zihui Sun; Panpan Wang; Haishu Chen; Tingting Gao; Qiangfeng Deng; Ziwen Wang; Qin Wang; Xiaoxiao Chen; Zhuowen Zhao; et al. (Drug Delivery and Translational Research, 2025)

Study on the antioxidant defense of Pacific oysters (Crassostrea gigas) against sulfonamide antibiotics - Hao Chen; Liping You; Jing Sun; Hao Yu; Wei Sun; Changlin Song; Bo Su; Chenglong Ji; Lin Ye; Shujun Li; Yanmin Qi; Yuanqing Ma (Aquaculture, 2025)

Superlinear control of phosphorus recycling in coastal sediments by organic matter availability - Jing Sun; Xiaotian Zhou; Yuxuan Lin; Xingyu Yang; Liuqian Yu; Charmaine C.M. Yung; Qiong Zhang; Jiying Li (Water Research, 2025)

Tripartite evolutionary game model for recycling strategies of decommissioned wind and solar energy equipment - Yifei Zhao; Minxi Wang; Jing Lin; Bei Sun; Xin Li (Waste Management, 2025)

The impact of wave-induced mixing on the simulation of the upper mixed layer in climate models - Yujie Jing; Jian Sun; Rui Li; Kejian Wu; Zipeng Yu; Pengfei Lin; Xianghui Dong; Alexander V. Babanin (Ocean Modelling, 2025)

Strontium diorthovanadate anode for fast-charging lithium-ion battery with low redox potential - Xiaolei Li; Shuangdui Wu; Jian Su; Jing Zhang; Xuguang An; Weitang Yao; Hongli Sun; Borong Lin; Qingquan Kong (Chemical Engineering Journal, 2025)

Perovskite-socketed FeCoNiCu quaternary alloy nanoparticles for efficient CO2 reduction in solid oxide electrolyzer - Shuo Liu; Lin-Bo Liu; Ming Yang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Single cobalt atoms anchored on in-situ-formed carbon layers within restricted microenvironment: an efficient catalyst for oxygen evolution reaction - Yang Wang; Ying Zhou; Xuan-Yi Liu; Xiao-Qin Zheng; Shui-Jing Wang; Kai Zhang; Xiang-Bin Shao; Jiahui Kou; Lin-Bing Sun (Chemical Engineering Journal, 2025)

Radial artery intima-media thickening is a sensitive marker of atherosclerosis and coronary artery stenosis, a lesson from a 6-year study of a spontaneous monkey model - Jue Wang; Wen Zheng; Haibao Shang; Lin Pan; Ye Yuan; Wenli Chen; Chunguang Guo; Shihan Li; Xueting Sun; Jing Guo; Xiuqin Zhang (Molecular and Cellular Biochemistry, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Updated insights into steady-modified anthocyanin food packaging: Novel strategies, characterization, application and future challenges - Jia-Yin Huang; Yu-Lei Chen; Duan-Quan Lin; Le-Chang Sun; Kang Liu; Ling-Jing Zhang; Ya-Qin Hu; Min-Jie Cao (Food Chemistry, 2025)

Description of Chrysonotomyia ophelimi sp. nov., Parasitoid of the Eucalyptus Gall Wasp Ophelimus bipolaris in China (Hymenoptera: Eulophidae) - Yuan-Hao Li; Jing-Hui Su; Jin Hu; Jin-Bo Sun; Yan Qin; Zoya Yefremova; Xia-Lin Zheng (Neotropical Entomology, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Fabrication of graphene-PEI composite membrane by supercritical CO2 exfoliation for efficient nanofiltration performance - Lin Li; Kunpeng Yu; Jing Xie; Haixin Sun; Tong Feng; Qinqin Xu; Jianzhong Yin (Chemical Engineering Journal, 2025)

Nitrogen level determines arbuscular mycorrhizal fungi nitrogen uptake rate of Stipa purpurea in alpine steppe - Jiahui Sun; Yu Tang; Keyu Chen; Shijie Ren; Hailan Shi; Qiang Dong; Junfu Dong; Lin Zhang; Xiaoyong Cui; Yanfen Wang; Baoming Ji; Jing Zhang (Plant and Soil, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Genetic Diversity Analysis of 89 Monogerm Maintainer Lines of Sugar Beet - Jing-Jing Zhao; Lin-Lin Sun; Zhi Pi; Sheng-Nan Li; Ze-Dong Wu (Sugar Tech, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Genome-based taxonomy of the family Haloarculaceae, proposal of Natronomonadaceae fam. nov., and description of four novel halophilic archaea from two saline lakes and a marine solar saltern - Ling-Rui Zhu; Ya-Ling Mao; Yao Hu; Ya-Ping Sun; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Island-like FeS2@TiO2 heterojunction modified separator for enhanced polysulfide management in lithium-sulfur batteries - Jing Song; Luchao Yue; Yifan Dou; Kun Yang; Lixin Zhang; Lin Jiang; Hongrui Liang; Yu Cao; Tianwei Fan; Xujie Zhang; Guisheng Qi; Xuping Sun; et al. (Chemical Engineering Journal, 2025)

SYMRK significantly affected AMF symbiosis and plant growth in maize - Jing Zhou; Sha Lin; Xinhao Luo; Lixue Sun; Jin Chen; Beijiu Cheng; Xiaoyu Li (Plant Science, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

Insight into selective removal of trace thallium (Tl(Ι)) by novel chitosan adsorbents encapsulating low-cost silicate mineral wastes - Yu Gong; Yujie Wang; Jing Yang; Yongxin Bing; Zifei Sun; Yongming Ju; Xiaochen Lin; Houhu Zhang; Zitao Lin; Weixin Li (Environmental Research, 2025)

Analytical method for laterally loaded offshore slender piles near sandy slopes considering slope deformation - Chong Jiang; Maolin Sun; Pan Liu; Mingke Lin; Jing Liu (Marine Georesources & Geotechnology, 2025)

Loss of KIFC1 activity induces spindle instability and actin defects during porcine oocyte maturation - Yu-Ran Wang; Peng-Jie Wang; Le-Yan Tao; Lin-Lin Hu; Qiang-Qiang Liu; Shao-Chen Sun; Jing-Xi Wei; Yue Wang (Theriogenology, 2025)

Sesquiterpenoids from Inula britannica and their potential mechanism for immunomodulation - Hui-Lin Zhang; Na Wang; Xu-Liu Shi; Miao-Miao Wang; Qi-Meng Zhu; Jing Chang; Yan-Li Feng; Juan Zhang; Feng Qiu; Cheng-Peng Sun (Phytochemistry, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Octopus-inspired multichannel tactile sensor for enhanced underwater material identification - Yutao Hao; Yanshuo Sun; Jing Wen; Xiaobo Gao; Yutong Wang; Zhiyuan Zhu; Zhong Lin Wang; Baodong Chen (Chemical Engineering Journal, 2025)

An arabinogalactan from Lycium barbarum mitigated DSS caused intestinal injury via inhibiting mucosal damage and regulating the gut microbiota disorder - Jiaojiao Mou; Jie Yang; Yanying Sun; Jing Liu; Yuxin Zhao; Hong Lin; Jianjun Yang (Carbohydrate Polymers, 2025)

Insufficient MIRO1 contributes to declined oocyte quality during reproductive aging - Zhen-Nan Pan; Hao-Lin Zhang; Kun-Huan Zhang; Jia-Qian Ju; Jing-Cai Liu; Shao-Chen Sun (Science China Life Sciences, 2025)

Synthesis and antibacterial activity of environmentally friendly sulfonium compounds - Jing Li; Wenyang Chen; Xinrui Bi; Yue Lin; Chengcai Liu; Yan Sun; Guinan Shen (Medicinal Chemistry Research, 2025)

Arsenic and its associated metabolism genes in Chinese soils: a comprehensive investigation of mine and paddy soils - Yu-Ting Lin; Rui-Lian Yu; Gong-Ren Hu; Jing-Wei Sun; Yu Yan (Journal of Soils and Sediments, 2025)

Study on Connectivity of Fractured-Vuggy Marine Carbonate Reservoirs Based on Dynamic and Static Methods - Yintao Zhang; Chengyan Lin; Lihua Ren; Chong Sun; Jing Li; Zhicheng Wang; Guojin Xu (Journal of Marine Science and Engineering, 2025)
Fractured-vuggy marine carbonate reservoirs, as an unconventional energy resource, hold significant potential for exploration and development. In this study, the Manshen block of the Furman oilfield in the Tarim Basin, China, was selected as the research object. A systematic investigation was conducted on the types of marine carbonate reservoir bodies, production characteristics, and both static and dynamic connectivity. Static connectivity analysis was performed using the heat diffusion equation and the multi-source potential field method. Dynamic connectivity evaluation was carried out by combining the dynamic time warping (DTW) algorithm with the analytic hierarchy process (AHP). Well logging, core analysis, and cast-thin section experiments were utilized to determine the types of reservoir spaces. The results indicate that the main types of reservoir spaces in the study area are caves, pores, and fractures. The fractures are primarily structural, with secondary development of dissolution fractures, weathering fractures, and sutures. The productivity changes in oil wells in the study area are classified into three types: slow decline, rapid decline, and high-speed decline. Based on the connectivity coefficients, wells were divided into three connectivity groups, with the A32 well group having the highest connectivity, followed by B5 well group 1, and B5 well group 2 having the lowest connectivity. The research provides technical support for the accurate evaluation of marine carbonate reservoirs and contributes to enhancing the efficiency of oil and gas exploration and development.

Long-term exposure to ambient air pollution and the incidence of systemic lupus erythematosus - Lihong Ye; Ding Ye; Yu Qian; Jiayu Li; Bin Liu; Jiacheng Ying; Manli Wang; Hao Lin; Jing Guo; Xiaohui Sun; Zhixing He; Chengping Wen; et al. (Chemosphere, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Discovering potential fumigants against Tribolium castaneum from essential oils using GC-MS and chemometric approaches - Yan Yan Lin; Min Xing Zhang; Miao Sun; Lu Sheng Wan; You Zhou; Jing Sheng Chen (Journal of Stored Products Research, 2025)

A pilot study on oral microbiome in electronic cigarettes consumers versus traditional cigarettes smokers - Jilong Liu; Qiulin Yue; Song Zhang; Jing Xu; Xingtao Jiang; Qun Su; Lei Sun; Baojun Li; Kunlun Li; Le Su; Lin Zhao (Folia Microbiologica, 2025)

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Exploring recycling strategies for retired wind turbine blades: The impact of policy subsidies and technological investments using a game-theoretic approach - Yifei Zhao; Minxi Wang; Jing Lin; Wei Liu; Lu Chen; Zheng Wang; Bei Sun; Xin Li (Journal of Cleaner Production, 2025)

Regulatory effects and mechanism of different selenium species on cadmium accumulation in Triticum aestivum L. (microbial response, gene expression and element accumulation) - Xuerong Di; Rui Jing; Xu Qin; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Environmental Research, 2025)

Constructing defect-rich CoO post smart Li extraction from spent Li-ion battery toward efficient oxygen evolution reaction - Shu-Ya Lei; Lin-Bo Liu; Subiao Liu; Wei Sun; Yue Yang; Jing-Li Luo (Chemical Engineering Journal, 2025)

Nitrogen mineralization/immobilization dynamics across the river-estuary-sea continuum: Effects of organic matter and microorganisms - Hengchen Wei; Peiyi Wang; Jing Li; Qingyan Wang; Fengwei Zhang; Dongyao Sun; Dengzhou Gao; Zhuhong Ding; Wei Du; Guoling Zhang; Xianbiao Lin (Marine Pollution Bulletin, 2024)

Global aerosol retrieval over land from Landsat imagery integrating Transformer and Google Earth Engine - Jing Wei; Zhihui Wang; Zhanqing Li; Zhengqiang Li; Shulin Pang; Xinyuan Xi; Maureen Cribb; Lin Sun (Remote Sensing of Environment, 2024)

AOPPs induces EMT and fibrosis by activating oxidative stress through ERK/p38 MAPK signaling pathway in endometriosis - Xiaoqing Luo; Sixi Wen; Junling Zeng; Jing Liu; Wenting Ye; Jiangpeng Wu; Songyu Huang; Wuwei Xie; Haiping Wen; Yan Sun; Jing Cai; Daidi Mo; et al. (Reproductive Biology, 2024)

Pulmonary surfactant biogenesis blockage mediated polyhexamethylene guanidine disinfectant induced pulmonary fibrosis - Xin Li; Jianzhong Zhang; Mingyue Wang; Haonan Li; Wanjun Zhang; Jiayin Sun; Lin Zhang; Yuxin Zheng; Jing Liu; Jinglong Tang (Journal of Hazardous Materials, 2024)

Investigating the robustness of microbial communities in municipal sludge anaerobic digestion under organic loading rate disturbance - Zong-Lin Wu; Wen-Jing Shi; Lin Zhang; Zi-Yuan Xia; Min Gou; Zhao-Yong Sun; Yue-Qin Tang (Journal of Environmental Management, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

The role of emulsion droplets and their interactions with other components in affecting the properties of active edible films: A review - Duanquan Lin; Le-Chang Sun; De-Xing Yao; Ling-Jing Zhang; Song Miao; Min-Jie Cao (Food Packaging and Shelf Life, 2024)

Enhancing the electrochemical performance of Ni-rich cathode through an in-situ La-doping and La4NiLiO8-coating synergistic strategy - Wei Zeng; Sheng-Qi Su; Ying-Min Qin; Jing-Zhe Wu; Jiang-Nan Ke; Yong-Gang Sun; Xi-Jie Lin (Chemical Engineering Journal, 2024)

Application of an α-galactosidase from Bacteroides fragilis on structural analysis of raffinose family oligosaccharides - Heyang Zu; Xuecui Yan; Jing Wu; Jingying Zhao; Kevin H. Mayo; Yifa Zhou; Liangnan Cui; Hairong Cheng; Lin Sun (Carbohydrate Polymers, 2024)

Oligosaccharides from Stellaria dichotoma L. var. lanceolate bind to galectin-3 and ameliorate effects of colitis - Zihan Zhao; Jing Wu; Xuejiao Xu; Zhen He; Xiang Wang; Jiyong Su; Kevin H. Mayo; Lin Sun; Liangnan Cui; Yifa Zhou (Carbohydrate Polymers, 2024)

Transcriptome profiling of longissimus dorsi during different prenatal stages to identify genes involved in intramuscular fat deposition in lean and obese pig breeds - Jun Feng Chen; Jing Wang; Jin Chai; Wei Jin; Qiao Ling Ren; Qiang Ma; Qing Xia Lu; Jia Jie Sun; De Lin Mo; Jia Qing Zhang; Bao Song Xing (Molecular Biology Reports, 2024)
Background There was significant difference in muscle development between fat-type and lean-type pig breeds. Methods and results In current study, transcriptome analysis and bioinformatics analysis were used to compare the difference in longissimus dorsi (LD) muscle at three time-points (38 days post coitus (dpc), 58 dpc, and 78 dpc ) between Huainan (HN) and Large white (LW) pig breeds. A total of 24500 transcripts were obtained in 18 samples, and 2319, 2799, and 3713 differently expressed genes (DEGs) were identified between these two breeds at 38 dpc, 58 dpc, and 78 dpc, respectively. And the number and foldchange of DEGs were increased, the alternative splice also increased. The cluster analysis of DEGs indicated the embryonic development progress of LD muscle between these two breeds was different. There were 539 shared DEGs between HN and LW at three stages, and the top-shared DEGs were associated with muscle development and lipid deposition, such as KLF4, NR4A1, HSP70, ZBTB16 and so on. Conclusions The results showed DEGs between Huainan (HN) and Large white (LW) pig breeds, and contributed to the understanding the muscle development difference between HN and LW, and provided basic materials for improvement of meat quality.

Pupil dilation and behavior as complementary measures of fear response in Mice - Jing Sun; Lin Zhu; Xiaojing Fang; Yong Tang; Yuci Xiao; Shaolei Jiang; Jianbang Lin; Yuantao Li (Cognitive Neurodynamics, 2024)

Circ-Luc7l Absence Attenuates Diabetic Nephropathy Progression by Reducing Mesangial Cell Excessive Proliferation, Inflammation, and Extracellular Matrix Accumulation via Mediating the miR-205-5p/Tgfbr1 Pathway - Zhan Fang; Dan Wang; Fang Sun; Jing Chang; Dong Yuan; Shuhua Lin; Jian Teng (Biochemical Genetics, 2024)

Alteromonas arenosi sp. nov., a novel bioflocculant-producing bacterium, isolated from intertidal sand - Bi Luo; Jing-Yun Su; Ya-Fei Zhang; Yong-Hui Xiao; Yun-Lin Peng; Mei-Ling Sun; Yi Li (Antonie van Leeuwenhoek, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Unveiling the occurrence and ecological risks of triclosan in surface water through meta-analysis - Zhenyao Wang; Xuan Li; Yi Li; Huan Liu; Carol Sze Ki Lin; Jing Sun; Qilin Wang (Environmental Pollution, 2024)

Synchronously enhanced flame retardancy and mechanical properties of polylactic acid via in-situ assembly of polyphosphazene nanoparticles on ammonium polyphosphate - Wei-hang Chen; De-xiang Sun; Duo-yang Zhang; Xiao-dong Qi; Jing-hui Yang; Lin Wang; Yong Wang (Chemical Engineering Journal, 2024)

Development of Ce-doped NH2-UiO-66(Zr) photocatalysts for efficient CO2 reduction in an aqueous system - Chao Yu; Xianjin Zhang; Chenxu Song; Yanna Wang; Jing Lin; Zhonglu Guo; Yujie Zhang; Zhenya Liu; Chunsheng Li; Yan Sun; Chengchun Tang; Yang Huang (Chemical Engineering Journal, 2024)

Exosomal miR-21-5p derived from endometrial stromal cells promotes angiogenesis by targeting TIMP3 in ovarian endometrial cysts - Liyuan Sun; Yan Cheng; Jing Wang; Di Wu; Lin Yuan; Xiaoyu Wei; Yan Li; Jie Gao; Guangmei Zhang (Journal of Molecular Medicine, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Complete chromium removal via photocatalytic reduction and adsorption using bimetallic UiO-66(Zr/Al) - Chao Yu; Chenxu Song; Xianjin Zhang; Yanna Wang; Jing Lin; Yang Huang; Zhonglu Guo; Chunsheng Li; Yujie Zhang; Zhenya Liu; Chengchun Tang; Yan Sun (Journal of Environmental Chemical Engineering, 2024)

Environmental water-mediated dual-mechanism regulation of PtCuδ-MnOx-catalyzed acetone oxidation: Enhancement of MvK and inhibition of L-H mechanism - Lei Wang; Xin Zhang; Yonggang Sun; Yulong Ma; Min Xu; Juan Zhang; Yingbo Zhu; Li Zhu; Song Qiao; Jing Ma; Jinpeng Wei; Feng Lin (Journal of Environmental Chemical Engineering, 2024)

Cellulose nanofiber powered interface engineering strategy to manufacture mechanically stable, moldable, recyclable, and biodegradable cellulose foam - Longfei Sun; Jing Lu; Xinxin Chen; Hanfei Zhao; Lin Liu; Juming Yao (Chemical Engineering Journal, 2024)

Characteristics of acidic hydrothermal treatment for disintegration of spiramycin fermentation residue and degradation of residual antibiotics - Gang Wang; Quancheng Shu; Jinzhi Sun; Yucan Liu; Xiaoyong Yang; Hao Lin; Jing Ding; Yanxiang Zhang; Lijuan Lan; Hongwei Sun (Bioresource Technology, 2024)

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Bladder cancer: non-coding RNAs and exosomal non-coding RNAs - Jingang Zhao; Yangyang Ma; Xiaodong Zheng; Zhen Sun; Hongxiang Lin; Chuanjun Du; Jing Cao (Functional & Integrative Genomics, 2024)

Exploring seasonal variations, assembly dynamics, and relationships of bacterial communities in different habitats of marine ranching - Cheng-Zhuang Chen; Ming-Hao Yin; Lin-Jing Niu; Jin-Xin Wang; Ling Liu; Yong-Jun Sun; Wen-Ming Ju; Ping Li; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Scalable-produced micro-elastic triboelectric sensing ground for all-weather large-scale applications - Xiaobo Gao; Fangjing Xing; Xiukun Hang; Feng Guo; Jing Wen; Wuliang Sun; Hao Song; Zhong Lin Wang; Baodong Chen (Chemical Engineering Journal, 2024)

QseC regulates chemotaxis, biofilm formation, motility, and virulence in Aeromonas veronii TH0426 - Luo-tao Tao; Lu Wang; Jing Xiong; Liang Chen; Ze-lin Zhao; Dong-xing Zhang; Lei Zhang; Wu-wen Sun; Xiao-feng Shan (Aquaculture, 2024)

The role and transcriptomic mechanism of cell wall in the mutual antagonized effects between selenium nanoparticles and cadmium in wheat - Xuerong Di; Rui Jing; Xu Qin; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Journal of Hazardous Materials, 2024)

Label analysis and molecular identification of Japanese Seafood Products purchased on Chinese e-commerce - Xia Zhang; Chiara Malloggi; Alice Giusti; Weide Deng; Zhenzhu Sun; Yuan Li; Jing Guo; Hongyuan Peng; Lara Tinacci; Lin Gao; Andrea Armani; Jing Wen (Food Control, 2024)

Multiscale rooftop greening and its socioeconomic implications in Hong Kong - Jing Ling; Ka Hei Anson Yip; Shan Wei; Ka Ying Sit; Liqun Sun; Qingyan Meng; Na Cong; Jian Lin; Hongsheng Zhang (Building and Environment, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Sophisticated construction of single-atom cobalt catalyst based on microbial hyphae for high-performance hydrogenation - Junhua Kuang; Minghao Gong; Gaofeng Chen; Li Peng; Chen Zou; Zhiqing Peng; Weiming Chen; Yin Li; Yuting Zhang; Tianwei Xue; Chuang Li; Yangyang Dong; et al. (Chemical Engineering Journal, 2024)

Kidney Function and Cardiovascular Disease: Evidence from Observational Studies and Mendelian Randomization Analyses - Wenjun Yang; Xuemei Wu; Manying Zhao; Jianying Hu; Chenhao Lin; Zhendong Mei; Jing Chen; Xu-jie Zhou; Sheng Nie; Jing Nie; Xiang Gao; Yan Zheng; et al. (Phenomics, 2024)

Long-term PM1 exposure and hypertension hospitalization: A causal inference study on a large community-based cohort in South China - Yuqin Zhang; Shirui Chen; Jing Wei; Jie Jiang; Xiao Lin; Ying Wang; Chun Hao; Wenjing Wu; Zhupei Yuan; Jie Sun; Han Wang; Zhicheng Du; et al. (Science Bulletin, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Comprehensive analysis of fresh tea (Camellia sinensis cv. Lingtou Dancong) leaf quality under different nitrogen fertilization regimes - Zihao Qiu; Jinmei Liao; Jiahao Chen; Ansheng Li; Minyao Lin; Hongmei Liu; Wei Huang; Binmei Sun; Jing Liu; Shaoqun Liu; Peng Zheng (Food Chemistry, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

PM2.5-induced premature senescence in HUVECs through the SIRT1/PGC-1α/SIRT3 pathway - Qing Yan; Rao Zheng; Yi Li; Juan Hu; Meidi Gong; Manman Lin; Xuecong Xu; Jing Wu; Shikun Sun (Science of The Total Environment, 2024)

Halorubrum hochsteinianum sp. nov., an ancient haloarchaeon from a natural experiment - Russell H. Vreeland; Ya-Ping Sun; Bei-Bei Wang; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Three-Dimensional Turbulent Simulation of Bivariate Normal Distribution Protection Device - Jing Liu; Zongyu Li; Hanming Huang; Weiwei Lin; Zhilin Sun; Fanjun Chen (Journal of Marine Science and Engineering, 2024)
In response to the deficiencies in existing bridge pier scour protection technologies, this paper introduces a novel protective device, namely a normal distribution-shaped surface (BND) protection devices formed by rotating a concave normal curve. A three-dimensional turbulent SST k−ω model is constructed, and physical model experiments of conical surfaces are conducted to validate the mathematical model. The simulation analyzes longitudinal water flow, downflow, vorticity intensity, and shear stress within normal and conical surfaces. The results show that the downflow distribution in front of the pier spans a relative water depth of (−0.45, 0.67), with a peak velocity approximately 70% of the longitudinal flow velocity. Circulation forms within the surfaces, with the main vortex flux inside the BND being 33% lower than that inside the conical surface. The maximum shear stress coefficient inside the BND can reach 9, and the protective surface isolates the bed from the flow to prevent scouring by high shear stress. The velocity gradient at the edge of the surface is small, and the edge shear stress of the 3D normal distribution-shaped surface (BND) protection device is only one-third of that of the conical surface, preventing edge scouring. The large shear stress and its distribution area decrease monotonically with the increase in surface width. When the surface width is four times the diameter, the distribution range of the shear stress coefficient greater than 1 is very small. The study of three-Dimensional turbulence within the BND provides a numerical basis for an anti-scour design.

Effects of production temperature on the molecular composition and seed-germination-promoting properties of sludge-based hydrochar-derived dissolved organic matter - Chuanjin Lin; Zhenhua Xin; Shijie Yuan; Jing Sun; Bin Dong; Zuxin Xu (Water Research, 2024)

Long-term biogas slurry application increases microbial necromass but not plant lignin contribution to soil organic carbon in paddy soils as regulated by fungal community - Zhaoming Chen; Jinchuan Ma; Junwei Ma; Jing Ye; Qiaogang Yu; Ping Zou; Wanchun Sun; Hui Lin; Feng Wang; Xinlin Zhao; Qiang Wang (Waste Management, 2024)

Tracking of the conversion and transformation pathways of dissolved organic matter in sludge hydrothermal liquids during Cr(VI) reduction using FT-ICR MS - Chuanjin Lin; Yanfei Tang; Jing Sun; Bin Dong; Xu Zuxin (Journal of Hazardous Materials, 2024)

Effect of EDDS on the rhizosphere ecology and microbial regulation of the Cd-Cr contaminated soil remediation using king grass combined with Piriformospora indica - Haixiang Zhang; Kailu Zhang; Yali Duan; Xiaoyan Sun; Li Lin; Qianli An; Muhammad Mohsin Altaf; Zhiqiang Zhu; Fan Liu; Yangqiu Jiao; Jing Yin; Can Xie; et al. (Journal of Hazardous Materials, 2024)

Chameleon-inspired supramolecular materials based on cucurbit[7]uril and viologens exhibiting full-color tunable photochromic behavior - Dong-Xue Xia; Xin Wang; Wen-Qi Sun; Rui-Lian Lin; Jing-Xin Liu; Ying-Wei Yang (Chemical Engineering Journal, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Sulfur atom-directed metal–ligand synergistic catalysis in zirconium/hafnium-oxo clusters for highly efficient amine oxidation - Sheng-Nan Sun; Qian Niu; Jiao-Min Lin; Li-Ling He; Jing-Wen Shi; Qing Huang; Jiang Liu; Ya-Qian Lan (Science Bulletin, 2024)

Rapid and efficient preparation of cationized lignin for downstream high value-added utilization of biodegradable antimicrobial nanofibrous membranes - Yu-Fei Gao; Cheng-Ye Ma; Qian Sun; Xin-Xu Zhang; Jing Liu; Jia-Long Wen; Rou-Xi Chen; Hsing-Lin Wang; Tong-Qi Yuan (Chemical Engineering Journal, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

White and Gray Matter Abnormalities in Young Adult Females with Dependent Personality Disorder: A Diffusion-Tensor Imaging and Voxel-Based Morphometry Study - Zhixia Cui; Liangliang Meng; Qing Zhang; Jing Lou; Yuan Lin; Yueji Sun (Brain Topography, 2024)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Functional polymorphisms in Benzo(a)Pyrene-induced toxicity pathways associated with the risk on laryngeal squamous cell carcinoma - Lin Xu; Xueying Sun; Yiyi Wang; Tao Zhou; Jingjing Jia; Mai Zhang; Pengyuan Zhou; Yixiao Wang; Youshuo Wang; Yingqing Shou; Xiaoyu Huo; Xiaoying Ji; et al. (Food and Chemical Toxicology, 2023)

Constructing gradient triboelectric charge to enhance power output for elastic-materials-based TENGs - Xiaobo Gao; Fangjing Xing; Feng Guo; Wuliang Sun; Jing Wen; Zhong Lin Wang; Baodong Chen (Chemical Engineering Journal, 2023)

Transcriptome analysis reveals the molecular mechanism of different forms of selenium in reducing cadmium uptake and accumulation in wheat seedlings - Xuerong Di; Rui Jing; Xu Qin; Yihua Wei; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Chemosphere, 2023)

Improved functionality and safety of peptides by the formation of peptide-polyphenol complexes - Duanquan Lin; Le-Chang Sun; Wei-Sen Huo; Ling-Jing Zhang; Yu-Lei Chen; Song Miao; Min-Jie Cao (Trends in Food Science & Technology, 2023)

Selective depression of pyrite with a novel thiocarbonate in a pyrite-galena flotation system - Gaogui Jing; Sheng Jian; Jianhua Chen; Shihong Xu; Wei Sun; Shangyong Lin; Zhiyong Gao (Minerals Engineering, 2023)

Arsenic exposure and lung function decline in chronic obstructive pulmonary disease patients: The mediating influence of systematic inflammation and oxidative stress - Yun-Feng Liu; Min-Min Tang; Jing Sun; Jia-Fei Li; Ya-Lin Jiang; Hui Zhao; Lin Fu (Food and Chemical Toxicology, 2023)

Nanocomposite hydrogel to deliver the immunomodulator lenalidomide and anti-inflammatory hesperidin locally to joints affected by rheumatoid arthritis - Xingjie Du; Yan Lin; Zheyu Shuai; Junfeng Duan; Changguang Wang; Junsheng Liu; Jun Jiang; Jianming Wu; Meiling Zhou; Zhirong Zhang; Zhongbing Liu; Xiangyu Zhou; et al. (Chemical Engineering Journal, 2023)

Enzyme-catalyzed electrochemical aptasensor for ultrasensitive detection of soluble PD-L1 in breast cancer based on decorated covalent organic frameworks and carbon nanotubes - Yue Zhang; Shuyi Chen; Jie Ma; Xiaobin Zhou; Xinchen Sun; Hongyun Jing; Mei Lin; Chenglin Zhou (Analytica Chimica Acta, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Ensemble machine learning reveals key structural and operational features governing ion selectivity of polyamide nanofiltration membranes - Dan Lu; Xuanchao Ma; Jiancong Lu; Yukun Qian; Yifang Geng; Jing Wang; Zhikan Yao; Lijun Liang; Zhilin Sun; Songmiao Liang; Lin Zhang (Desalination, 2023)

Anisotropic aptamer-modified DNA tetrahedra/MOF nanoprobes for enhanced colorimetric aptasensing of cardiac troponin I - Lizhu Zeng; Chenjia Lin; Peiqing Liu; Duanping Sun; Jing Lu (Chemical Engineering Journal, 2023)

Glutathione-Responsive Sulfur Dioxide-Releasing Dendronized Chitooligosaccharide Polymer for Effective Treatment of Multidrug-Resistant Bacterial Infection - Haitao Yu; Jiejiao Liu; Qianwen Lin; Jun Liu; Siming Yu; Pinghua Sun; Jing Lin (Chemical Engineering Journal, 2023)

Dynamic characteristics of heavy metal accumulation in agricultural soils after continuous organic fertilizer application: Field-scale monitoring - Wanchun Sun; Jing Ye; Hui Lin; Qiaogang Yu; Qiang Wang; Zhaoming Chen; Jinchuan Ma; Junwei Ma (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Properties of Pacific white shrimp (Litopenaeus vannamei) collagen and its degradation by endogenous proteinases during cold storage - Xu-Chen Xiao; Duanquan Lin; Kai-Yuan Cao; Le-Chang Sun; Yu-Lei Chen; Ling Weng; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Tissue residue distribution and withdrawal time estimation of trimethoprim and sulfachloropyridazine in Yugan black-bone fowl ( Gallus gallus domesticus Brisson) - Lin Zhao; Dawen Zhang; Jing Lan; Xiangdong Sun; Yun Zhang; Bing Wang; Bei Ni; Shuang Wu; Ruiying Zhang; Hui Liao (Food Additives & Contaminants: Part A, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

Removal of chemical oxygen demand and ammonia nitrogen from high salinity tungsten smelting wastewater by one-step electrochemical oxidation: From bench-scale test, pilot-scale test, to industrial test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Huanjun Bao; Meirong Wu; Lei Yang; Gaogui Jing; Haisheng Han; Chenyang Zhang; Xiaoyun Jiang; Songlin Wang; Wei Ding; et al. (Journal of Environmental Management, 2023)

Association of the components of ambient fine particulate matter (PM2.5) and chronic kidney disease prevalence in China - Xingyuan Zhang; Jiayi Tao; Fang Lei; Tao Sun; Lijin Lin; Xuewei Huang; Peng Zhang; Yan-Xiao Ji; Jingjing Cai; Xiao-Jing Zhang; Hongliang Li (Journal of Environmental Management, 2023)

V-ATPase V0 subunit activation mediates maduramicin-induced methuosis through blocking endolysosomal trafficking in vitro and in vivo - Yuling Zheng; Jing Xiao; Junqi Wang; Bin Dong; Dawei Guo; Hui Ji; Haifeng Sun; Lin Peng; Shanxiang Jiang; Xiuge Gao (Food and Chemical Toxicology, 2023)

Benchmark dose estimation for benzene-exposed workers in China: Based on quantitative and multi-endpoint genotoxicity assessments - Yiyi Cao; Tongshuai Wang; Jing Xi; Wei Tian; Weiying Liu; Yuan Sun; Wuzhong Liu; Xinyue You; Anqi Li; Guanghui Zhang; XinYu Zhang; Zhao-lin Xia; et al. (Environmental Pollution, 2023)

Drip fertigation with straw incorporation promotes soil microbial network complexity and potentially reduces pathogen abundance in greenhouse vegetable production systems - Jing Hu; Yifei Sun; Meiju Liu; Yiming Zhao; Haofeng Lv; Yafang Wang; Guoyuan Li; Jingguo Wang; Klaus Butterbach-Bahl; Shan Lin (Agriculture, Ecosystems & Environment, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

WITHDRAWN: Evaluation of the effects of e-cigarette aerosol extracts and tobacco cigarette smoke extracts on human gingival epithelial cells - Le Su; Jilong Liu; Qiulin Yue; Song Zhang; Chen Zhao; Xin Sun; Jing Xu; Xingtao Jiang; Kunlun Li; Baojun Li; Lin Zhao (Toxicology in Vitro, 2023)

OsCIP1, a secreted protein, binds to and stabilizes OsCR4 to promote aleurone layer development, seed germination and early seedling growth in rice - Lin-Lin Yan; Jing Mi; Can-Can Shen; Rong Qian; Jiao Wang; Cui-Xia Pu; Ying Sun (Plant Science, 2023)

Exposure to acrylamide induces zygotic genome activation defects of mouse embryos - Si-Le Wu; Jia-Qian Ju; Yi-Ming Ji; Hao-Lin Zhang; Yuan-Jing Zou; Shao-Chen Sun (Food and Chemical Toxicology, 2023)

Point defect engineering of elemental phosphorus for photocatalytic hydrogen evolution - Yajie Sun; Xinya Pei; Bo Wang; Yun Hau Ng; Ruixue Zhu; Qichao Zhang; Jiguang Deng; Yuxi Liu; Lin Jing; Hongxing Dai (Chemical Engineering Journal, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Mechanism study on gliding arc (GA) plasma reforming: Reaction and energy pathways for H2 production from methanol steam reforming - Zhuo-Wen Xue; Jing-Lin Liu; Zhi-Yuan Zhang; Hemedi Kitila; Hao-Yu Lian; Bing Sun; Ai-Min Zhu (Chemical Engineering Journal, 2023)

Molecular engineering of Fe-MIL-53 electrocatalyst for effective oxygen evolution reaction - Yue Wang; Zhiyi Zhou; Yuzhi Lin; Yongzheng Zhang; Peiyan Bi; Qiqi Jing; Yidong Luo; Zhaodi Sun; Jiajun Liao; Zhi Gao (Chemical Engineering Journal, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Halocatena marina sp. nov., a novel filamentous halophilic archaeon isolated from marine tidal flat and emended description of the genus Halocatena - Zhang-Ping Wu; Xi-Wen Zheng; Ya-Ping Sun; Bei-Bei Wang; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Establishing a high-performance anti-fouling PEI-ZIF-PAA membrane with improved Lewis acid-base interactions and hydrophilicity - Zhang-Hong Wan; Jing Guan; Chun-Miao Zhang; Wen-Qing Fei; Lin Wang; Shu-Guang Wang; Xue-Fei Sun (Chemosphere, 2023)

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

Metal ions synergize with gangue minerals to remove residual sodium oleate from mineral processing wastewater - Xiangsong Meng; Min Jiang; Shangyong Lin; Zhiyong Gao; Haisheng Han; Li Wang; Chenyang Zhang; Ruohua Liu; Huanjun Bao; Meirong Wu; Gaogui Jing; Wei Sun (Journal of Cleaner Production, 2023)

Gestation and lactation triphenyl phosphate exposure disturbs offspring gut microbiota in a sex-dependent pathway - Xiaoshan Liu; Juntong Lin; Yuting Chen; Mengzhu Jiang; Qian Liu; Jing Zhang; Xiaoxun Lu; Jiabin Hong; Wenjing Sun; Yanqin Sun; Lianxian Guo (Food and Chemical Toxicology, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Halorarius litoreus gen. nov., sp. nov., Halorarius halobius sp. nov., Haloglomus halophilum sp. nov., Haloglomus salinum sp. nov., and Natronomonas marina sp. nov., extremely halophilic archaea isolated from tidal flat and marine solar salt - Ya-Ping Sun; Bei-Bei Wang; Zhang-Ping Wu; Xi-Wen Zheng; Jing Hou; Heng-Lin Cui (Frontiers in Marine Science, 2023)
Five novel halophilic archaeal strains, named BND22 T , ZY10 T , ZY41 T , ZY58 T , and ZY43 T , were isolated from the coastal saline sediment of the intertidal zone located in Qingdao and the natural sea salt produced from Huanghua marine solar saltern, PRChina. These five strains demonstrated the typical morphology and growth characteristics of haloarchaea. The comparison of 16S rRNA gene revealed that strain BDN22 T was associated with Salinirubellus salinus ZS-35-S2 T (95.2% similarity), strain ZY10 T was related to Halosegnis rubeus F17-44 T (95.1% similarity), both strains ZY41 T and ZY58 T were closely related to Haloglomus irregulare F16-60 T (98.1% and 98.2% similarities, respectively), and strain ZY43 T was close to Natronomonas salina YPL13 T (98.0% similarity). In addition to the 16S rRNA gene, the rpoB′ gene is undoubtedly another important molecular marker for the identification of halophilic archaea, and concatenated-conserved-protein phylogeny was widely used in archaeal classification in recent years. Phylogenetic and phylogenomic analyses based on rpoB′ genes and 122 concatenated archaeal protein genes showed that these haloarchaea construct three different clades and gathered together with the current members of Haloarculaceae . Strains BND22 T and ZY10 T formed two distinct clades separated from Salinirubellus salinus ZS-35-S2 T and Halosegnis members, strains ZY41 T and ZY58 T clustered with Haloglomus irregulare F16-60 T , and strain ZY43 T gathered with the current members of Natronomonas. The ANI, DDH, and AAI values of these five strains against phylogenetic neighbours were no more than 91%, 45%, and 92%, respectively, far below the cut-off values for species delineation, supporting their placements in new taxa. Based on the phenotypic, chemotaxonomic, phylogenetic, and phylogenomic properties, these five strains represent five novel taxa of the family Haloarculaceae , Halorarius litoreus gen. nov., sp. nov. (type strain BND22 T = CGMCC 1.18780 T = JCM 34966 T ), Halorarius halobius sp. nov. (type strain ZY10 T = CGMCC 1.17475 T = JCM 34319 T ), Haloglomus halophilum sp. nov. (type strain ZY41 T = CGMCC 1.17030 T = JCM 34161 T ), Haloglomus salinum sp. nov. (type strain ZY58 T = CGMCC 1.17216 T = JCM 34163 T ), and Natronomonas marina sp. nov. (type strain ZY43 T = CGMCC 1.17202 T = JCM 34162 T ). This is the first report of description of a novel haloarchaeon isolated from a marine intertidal zone.

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Impacts of hydraulic conditions on microplastics biofilm development, shear stresses distribution, and microbial community structures in drinking water distribution pipes - Xiao Chen; Xiao-ying Lian; Yi Wang; Sheng Chen; Yi-ran Sun; Guo-lin Tao; Qiao-wen Tan; Jing-chun Feng (Journal of Environmental Management, 2023)

A microscale regulation strategy for strong, tough, and efficiently self-healing energetic adhesives - Jing Yang; Xin Zhou; Junqing Yang; Jiaoyang Chen; Zhe Sun; Yuhang Cheng; Lin Yang; Hui Wang; Guangpu Zhang; Jiajun Fu; Wei Jiang (Chemical Engineering Journal, 2023)

Nanocellulose interface enhanced all-cellulose foam with controllable strength via a facile liquid phase exchange route - Longfei Sun; Lin Liu; Mingbang Wu; Dengfeng Wang; Rongsheng Shen; Hanfei Zhao; Jing Lu; Juming Yao (Carbohydrate Polymers, 2023)

Halorussus vallis sp. nov., Halorussus aquaticus sp. nov., Halorussus gelatinilyticus sp. nov., Halorussus limi sp. nov., Halorussus salilacus sp. nov., Halorussus salinisoli sp. nov.: six extremely halophilic archaea isolated from solar saltern, salt lake and saline soil - Xi-Wen Zheng; Zhang-Ping Wu; Ya-Ping Sun; Bei-Bei Wang; Jing Hou; Heng-Lin Cui (Extremophiles, 2022)

Halorientalis salina sp. nov., Halorientalis marina sp. nov., Halorientalis litorea sp. nov.: three extremely halophilic archaea isolated from a salt lake and coarse sea salt - Bei-Bei Wang; Ya-Ping Sun; Zhang-Ping Wu; Xi-Wen Zheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2022)

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

Development of diagnostic molecular markers to differentiate sharp eyespot and Fusarium crown rot isolates collected from common wheat fields in China - Yan Ren; Yue Wang; Li-yan Wang; Xia-Lei Lv; Ti Liu; Jing-yun Nie; Peng Guo; Lin Ma; Xiao-nan Sun; Feng Chen (Phytoparasitica, 2022)

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

Reading-related Brain Function Restored to Normal After Articulation Training in Patients with Cleft Lip and Palate: An fMRI Study - Liwei Sun; Wenjing Zhang; Mengyue Wang; Songjian Wang; Zhen Li; Cui Zhao; Meng Lin; Qian Si; Xia Li; Ying Liang; Jing Wei; Xu Zhang; et al. (Neuroscience Bulletin, 2022)

Effect of straw biochar from different crops on growth and nutrient uptake by peach (Prunus davidiana) seedlings - Qin Liu; Haoran Zhang; Yan Wang; Jing Sun; Dong Chen; Meiyan Tu; Lijin Lin (Acta Physiologiae Plantarum, 2022)

Novel Self-Assembled Micelles With Increased Tumor Penetration and Anti-Tumor Efficiency Against Breast Cancer - Yani Yang; Yuezhu Zhao; Jie Liu; Chen Ge; Weiwei Zhang; Yue Zhang; Junji Wang; Guohao Sun; Xiujun Lin; Xiaohong Lu; Xiang Tang; Jun He; et al. (Pharmaceutical Research, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Identification and molecular mapping of YrBm for adult plan resistance to stripe rust in Chinese wheat landrace Baimangmai - Chaoyue Hu; Fengtao Wang; Jing Feng; Cai Sun; Jiyuan Guo; Xiaowei Lang; Jinghuang Hu; Bin Bai; Wentao Zhang; Hongjie Li; Ruiming Lin; Shichang Xu (Theoretical and Applied Genetics, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Isolation and identification of two new sargentodoxosides from Sargentodoxa cuneata and their agonistic effects against FXR - Wen Zhang; Cheng-Peng Sun; Yu-Lin Peng; Wen-Yu Zhao; Zheng-Yue Wang; Jing Ning; Xia Lv; Zhen-Long Yu; Shuang Zhou; Wei Peng; Bang-Jiang Fang; Xiao-Chi Ma (Natural Product Research, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Proteomic characterization of four subtypes of M2 macrophages derived from human THP-1 cells - Pengfei Li; Chen Ma; Jing Li; Shanshan You; Liuyi Dang; Jingyu Wu; Zhifang Hao; Jun Li; Yuan Zhi; Lin Chen; Shisheng Sun (Journal of Zhejiang University-SCIENCE B, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

The Flavor and Antioxidant Activity Change Pattern of Shrimp Head Paste During Fermentation - Jing Yu; Kuan Lu; Jinyuan Sun; Wancui Xie; Lin Song; Hongxia Che (Journal of Ocean University of China, 2022)

Characterizing the Role of Glutamine synthetase Gene on Ammonia Nitrogen Detoxification Metabolism of the Razor Clam Sinonovacula constricta - Gaigai Sun; Changsen Sun; Jing He; Hanhan Yao; Wenfang Dai; Zhihua Lin; Yinghui Dong (Frontiers in Marine Science, 2021)
Ammonia nitrogen is a common toxic substance in the aquatic system, which seriously threatens the survival and growth of clams. However, less is known about the ammonia metabolism and detoxification strategy in razor clam. In this study, the polymorphism of the Glutamine synthetase gene from Sinonovacula constricta ( Sc-GS ) was found to be related to ammonia tolerance. By comparing the coding sequence (CDS) region of Sc-GS from two geographical populations, a total of 14 and 12 single nucleotide polymorphisms (SNPs) were identified, respectively, of which 10 loci were shared between the two populations. Among them, the locus c.1133T > G exhibited an extremely significant and strong association with ammonia tolerance in both populations ( P < 0.01), and it was missense mutation, which led to the amino acid change from leucine (Leu) to arginine (Arg). Furthermore, the results about H&E staining and immunohistochemistry of Sc-GS protein in gills and hepatopancreas revealed that it was specifically localized in the lateral cilia of gill filaments and the endothelial cells of hepatocytes. After inhibiting the Sc-GS expression by RNA interference (RNAi) technology, the transcript levels of Sc-GS were extremely significantly downregulated at 24, 48, 72, and 96 h ( P < 0.01) in the hepatopancreas. Taken together, these results indicated that the Sc-GS gene may participate in ammonia metabolism. In addition, these results will help to demonstrate the role of Sc-GS in ammonia nitrogen metabolism and provide markers related to ammonia nitrogen tolerance for molecular marker-assisted selection (MAS) of the razor clam.

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Phenolic glycosides and flavonoids with antioxidant and anticancer activities from Desmodium caudatum - Qian-Nan Xu; Dan Zhu; Guang-Hui Wang; Ting Lin; Cui-Ling Sun; Rong Ding; Wen-Jing Tian; Hai-Feng Chen (Natural Product Research, 2021)

How do different nitrogen application levels and irrigation practices impact biological nitrogen fixation and its distribution in paddy system? - Yanhui Zhang; Tianlong Hu; Hui Wang; Haiyang Jin; Qi Liu; Zhibin Lin; Benjuan Liu; Hongtao Liu; Zhe Chen; Xinwu Lin; Xiaojie Wang; Jing Ma; et al. (Plant and Soil, 2021)

Conversion of rice husk into fermentable sugar and silica using acid-catalyzed ionic liquid pretreatment - YuJie Wang; Jing-yong Liu; Jian Sun; Sumarlin Shangdiar; Kassian T.T. Amesho; Yung-Chang Lin; Yen-Ping Peng; Ken-Lin Chang (Environmental Science and Pollution Research, 2021)

An Improved DDV Algorithm for the Retrieval of Aerosol Optical Depth From NOAA/AVHRR Data - Ruibo Li; Lin Sun; Huiyong Yu; Jing Wei; Xinpeng Tian (Journal of the Indian Society of Remote Sensing, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Influences of organic material application on the physically separated soil organic carbon and nitrogen fractions in rice fields - Qiaogang Yu; Jing Ye; Wanchun Sun; Hui Lin; Qiang Wang; Junwei Ma (Journal of Soils and Sediments, 2021)

Preliminary study on relationships among nutritional risk, serum prealbumin, and peripheral blood T cell subsets in patients with severe COVID-19 - Yanli Li; Yanbo Sun; Jing He; Peng Zhao; Pengju Luo; Jinsong Bai; Weiming Li; Shumin Li; Yueying Lin; Yunyun Cen (Infectious Diseases, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Melatonin ameliorates spatial memory and motor deficits via preserving the integrity of cortical and hippocampal dendritic spine morphology in mice with neurotrauma - Xiao-Jing Lin; Ruoxu Liu; Chenyi Li; Xueqing Yi; Bo Fu; M. J. Walker; Xiao-Ming Xu; Gang Sun; Cheng-Hsien Lin (Inflammopharmacology, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

MicroRNA-761 modulates foam cell formation and inflammation through autophagy in the progression of atherosclerosis - Chao Wang; Wei Yang; Xiaofei Liang; Wei Song; Jing Lin; Yan Sun; Xiuru Guan (Molecular and Cellular Biochemistry, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Selenium accumulation characteristics of Cyphomandra betacea (Solanum betaceum) seedlings - Linjin Lin; Jing Sun; Tonghao Cui; Xiong Zhou; Ming’an Liao; Yunmin Huan; Liu Yang; Caifang Wu; Xianmin Xia; Yuxi Wang; Zhiyu Li; Jinpeng Zhu; et al. (Physiology and Molecular Biology of Plants, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Prevalence of RNF213 variants in symptomatic intracranial arterial stenosis/occlusion in China - Xunsha Sun; Man Luo; Jiaoxing Li; Rong Lai; Jing Lin; Yufang Wang; Xiaowei Xu; Shaoqing Wu; Wenli Sheng (Molecular Genetics and Genomics, 2020)

Effects of Dietary Supplementation of Recombinant Plectasin on Growth Performance, Intestinal Health and Innate Immunity Response in Broilers - Jing Lin Ma; Li Hua Zhao; Dan Dan Sun; Jing Zhang; Yong Peng Guo; Zhi Qiang Zhang; Qiu Gang Ma; Cheng Ji; Li Hong Zhao (Probiotics and Antimicrobial Proteins, 2020)

Involvement of the JNK signaling in granular corneal dystrophy by modulating TGF-β-induced TGFBI expression and corneal fibroblast apoptosis - Danyao Nie; Xinhua Liu; Yuan Wang; Wenling He; Ming Li; Yun Peng; Jing Zhang; Liangnan Sun; Zonghui Yan; Lin Ye (In Vitro Cellular & Developmental Biology - Animal, 2020)

Satellite data cloud detection using deep learning supported by hyperspectral data - Lin Sun; Xu Yang; Shangfeng Jia; Chen Jia; Quan Wang; Xinyan Liu; Jing Wei; Xueying Zhou (International Journal of Remote Sensing, 2020)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

Construction of High-Density Genetic Map and Mapping of Sex-Related Loci in the Yellow Catfish (Pelteobagrus fulvidraco) - Dong Gao; Min Zheng; Genmei Lin; Wenyu Fang; Jing Huang; Jianguo Lu; Xiaowen Sun (Marine Biotechnology, 2020)

Soil microbial activity and community composition as influenced by application of pig biogas slurry in paddy field in southeast China - Zhaoming Chen; Qiang Wang; Junwei Ma; Stephen Chapman; Ping Zou; Jing Ye; Qiaogang Yu; Wanchun Sun; Hui Lin; Lina Jiang (Paddy and Water Environment, 2020)

Probiotic Clostridium butyricum Improves the Growth Performance, Immune Function, and Gut Microbiota of Weaning Rex Rabbits - Lei Liu; Dong Zeng; Mingyue Yang; Bin Wen; Jing Lai; Yi Zhou; Hao Sun; Lvcheng Xiong; Jie Wang; Yicen Lin; Kangcheng Pan; Bo Jing; et al. (Probiotics and Antimicrobial Proteins, 2019)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Investigation of Lactic Acid Bacteria Isolated from Giant Panda Feces for Potential Probiotics In Vitro - Qian Liu; Xueqin Ni; Qiang Wang; Zhirong Peng; Lili Niu; Meiling Xie; Yicen Lin; Yi Zhou; Hao Sun; Kangcheng Pan; Bo Jing; Dong Zeng (Probiotics and Antimicrobial Proteins, 2019)

Genome-wide analysis identified 17 new loci influencing intraocular pressure in Chinese population - Lulin Huang; Yuhong Chen; Ying Lin; Pancy O. S. Tam; Yilian Cheng; Yi Shi; Bo Gong; Fang Lu; Jialiang Yang; Haixin Wang; Yi Yin; Yong Cao; et al. (Science China Life Sciences, 2019)

Assessment of anti-diabetic activity of peanut shell polyphenol extracts - Xiao-meng Sun; Hai-qing Ye; Jing-bo Liu; Lei Wu; Ding-bo Lin; Ya-li Yu; Feng Gao (Journal of Zhejiang University-SCIENCE B, 2018)

Analysis of fecal microbiota in patients with functional constipation undergoing treatment with synbiotics - Lin Sheng Huang; Cheng Kong; Ren Yuan Gao; Xuebing Yan; Hong Jing Yu; Bin Wen; Qi Zhu; Tong Yi Shen; Zhen Liang Sun; Huan Long Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Mechanical stress promotes matrix synthesis of mandibular condylar cartilage via the RKIP-ERK pathway - Lian Sun; Jing Zhao; Hua Wang; Yongchu Pan; Lin Wang; Wei-Bing Zhang (Journal of Molecular Histology, 2017)

Low-dose combined exposure of nanoparticles and heavy metal compared with PM2.5 in human myocardial AC16 cells - Lin Feng; Xiaozhe Yang; Collins Otieno Asweto; Jing Wu; Yannan Zhang; Hejing Hu; Yanfeng Shi; Junchao Duan; Zhiwei Sun (Environmental Science and Pollution Research, 2017)

Fine particle matters induce DNA damage and G2/M cell cycle arrest in human bronchial epithelial BEAS-2B cells - Jing Wu; Yanfeng Shi; Collins Otieno Asweto; Lin Feng; Xiaozhe Yang; Yannan Zhang; Hejing Hu; Junchao Duan; Zhiwei Sun (Environmental Science and Pollution Research, 2017)

The association study of nonsyndromic cleft lip with or without cleft palate identified risk variants of the $$\varvec{GLI3}$$ G L I 3 gene in a Chinese population - Yirui Wang; Yimin Sun; Yongqing Huang; Yongchu Pan; Bing Shi; Jian Ma; Lan Ma; Feifei Lan; Yuxi Zhou; Jiayu Shi; Jinfang Zhu; Hongbing Jiang; et al. (Journal of Genetics, 2017)

The analgesic effect of trans-resveratrol is regulated by calcium channels in the hippocampus of mice - Weijie Wang; Yingcong Yu; Jing Li; Lin Wang; Zhi Li; Chong Zhang; Linlin Zhen; Lianshu Ding; Gang Wang; Xiaoyang Sun; Ying Xu (Metabolic Brain Disease, 2017)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Genome-wide transcriptional analysis of cardiovascular-related genes and pathways induced by PM2.5 in human myocardial cells - Lin Feng; Xiaozhe Yang; Collins Otieno Asweto; Jing Wu; Yannan Zhang; Hejing Hu; Yanfeng Shi; Junchao Duan; Zhiwei Sun (Environmental Science and Pollution Research, 2017)

Anti-neuroinflammatory constituents from the fungus Penicillium purpurogenum MHZ 111 - Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Yi Ren; Dan Dong; Jiao Zheng; Ting Liu; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Oceanic currents drove population genetic connectivity of the brown alga Sargassum thunbergii in the north‐west Pacific - Jing‐Jing Li; Zi‐Min Hu; Xu Gao; Zhong‐Min Sun; Han‐Gil Choi; De‐Lin Duan; Hikaru Endo (Journal of Biogeography, 2017)
Aim Oceanic currents are among the most pervasive hydrodynamic features in shaping community dynamics, population connectivity and phylogeographical structure of intertidal species. Here, we test whether population structure and biogeographical gradients of genetic diversity in the brown alga Sargassum thunbergii are correlated with oceanic currents in the north‐west Pacific ( NWP ). Location North‐west Pacific (25.07°N–43.36°N). Methods Nuclear internal transcribed spacer‐2 and mitochondrial cox 3 sequences were obtained from 835 and 810 individuals of S. thunbergii respectively. Parsimony networks and phylogenetic trees (maximum parsimony and Bayesian inference) were constructed to evaluate phylogeographical structure. Pairwise F ST estimates and analyses of molecular variance ( AMOVA ) at various hierarchical levels (latitude, longitude, marine provinces, biogeographical basins and zoogeographical zones) were conducted to elucidate population genetic differentiation. migrate software was used to estimate the number of migrants between adjacent populations. Results Several lines of evidence indicate that S. thunbergii is characterized by shallow population structure. Geographical distances do not correlate with population pairwise genetic differentiations. The corridor/stepping‐stone model‐based coalescent analyses reveal high levels of asymmetric gene flow among S. thunbergii populations, with the numbers of migrants largely corresponding to the directions of oceanic current systems in the NWP . Genetic signatures also indicate that Jeju Island, Korea might act as a transition zone for dispersal of S. thunbergii in the NWP driven by the Kuroshio Current, thus facilitating subsequent transportation northward into the Sea of Japan and the Yellow‐Bohai Sea. Main conclusions Population genetic homogeneity in S. thunbergii was mainly structured by oceanic currents rather than palaeoclimatic events. Our study illustrates an important phylogeographical case of how coastal hydrodynamic factors contributed to population connectivity and geographical shifts of genetic diversity for marine organisms without a pelagic stage.

Equisetum cf. oppositum (Equisetaceae) from the Paleocene-Eocene of Tibet in southwestern China and its paleoenvironmental implications - Guo-Lin Yang; Zi-Xi Wang; Jing-Wei Chen; De-Fei Yan; Bai-Nian Sun (Arabian Journal of Geosciences, 2016)

Co-exposure to amorphous silica nanoparticles and benzo[a]pyrene at low level in human bronchial epithelial BEAS-2B cells - Jing Wu; Yanfeng Shi; Collins Otieno Asweto; Lin Feng; Xiaozhe Yang; Yannan Zhang; Hejing Hu; Junchao Duan; Zhiwei Sun (Environmental Science and Pollution Research, 2016)

Minocycline ameliorates d-galactose-induced memory deficits and loss of Arc/Arg3.1 expression - Xu Li; Fen Lu; Wei Li; Jun Xu; Xiao-Jing Sun; Ling-Zhi Qin; Qian-Lin Zhang; Yong Yao; Qing-Kai Yu; Xin-Liang Liang (Molecular Biology Reports, 2016)

MicroRNA-99a regulates early chondrogenic differentiation of rat mesenchymal stem cells by targeting the BMPR2 gene - Xiaozhong Zhou; Jing Wang; Hongtao Sun; Yong Qi; Wangyang Xu; Dixin Luo; Xunjie Jin; Chao Li; Weijian Chen; Zhousheng Lin; Feimeng Li; Ran Zhang; et al. (Cell and Tissue Research, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Oxidation of aniline aerofloat in flotation wastewater by sodium hypochlorite solution - Weixiong Lin; Jing Tian; Jie Ren; Pingting Xu; Yongkang Dai; Shuiyu Sun; Chun Wu (Environmental Science and Pollution Research, 2016)

Spontaneous white matter lesion in brain of stroke-prone renovascular hypertensive rats: a study from MRI, pathology and behavior - Yuhua Fan; Linfang Lan; Lu Zheng; Xiaotan Ji; Jing Lin; Jinsheng Zeng; Ruxun Huang; Jian Sun (Metabolic Brain Disease, 2015)

Heavy metal contamination of agricultural soils affected by mining activities around the Ganxi River in Chenzhou, Southern China - Li Ma; Jing Sun; Zhaoguang Yang; Lin Wang (Environmental Monitoring and Assessment, 2015)

Wide-angle incidence and P-wave transmission - Jun-Fa Xie; Cheng-Yu Sun; Mei-Yan Lin; Jing-Jing Li (Applied Geophysics, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Phylogeographic structure and deep lineage diversification of the red alga Chondrus ocellatus Holmes in the Northwest Pacific - Zi‐Min Hu; Jing‐Jing Li; Zhong‐Min Sun; Jung‐Hyun Oak; Jie Zhang; Pablo Fresia; W. Stewart Grant; De‐Lin Duan (Molecular Ecology, 2015)
A major goal of phylogeographic analysis using molecular markers is to understand the ecological and historical variables that influence genetic diversity within a species. Here, we used sequences of the mitochondrial Cox 1 gene and nuclear internal transcribed spacer to reconstruct its phylogeography and demographic history of the intertidal red seaweed Chondrus ocellatus over most of its geographical range in the Northwest Pacific. We found three deeply separated lineages A, B and C, which diverged from one another in the early Pliocene–late Miocene ( c . 4.5–7.7 Ma). The remarkably deep divergences, both within and between lineages, appear to have resulted from ancient isolations, accelerated by random drift and limited genetic exchange between regions. The disjunct distributions of lineages A and C along the coasts of Japan may reflect divergence during isolation in scattered refugia. The distribution of lineage B, from the South China Sea to the Korean Peninsula, appears to reflect postglacial recolonizations of coastal habitats. These three lineages do not coincide with the three documented morphological formae in C. ocellatus , suggesting that additional cryptic species may exist in this taxon. Our study illustrates the interaction of environmental variability and demographic processes in producing lineage diversification in an intertidal seaweed and highlights the importance of phylogeographic approaches for discovering cryptic marine biodiversity.

Haloarchaeobius amylolyticus sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Xin-Juan Sun; Xi Liang; Xiao-Jing Chen; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2015)

A large-scale breeding experiment and observations on development of Cyanea nozakii (Scyphozoa, Cyaneidae) from fertilized eggs to larval medusae - Chun-sheng Liu; Zhi-meng Zhuang; Si-qing Chen; Jing-ping Yan; Chang-lin Liu; Jian-ming Sun (Hydrobiologia, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Systemic nematicidal activity and biocontrol efficacy of Bacillus firmus against the root-knot nematode Meloidogyne incognita - Jing Xiong; Qiaoni Zhou; Haiyan Luo; Liqiu Xia; Lin Li; Ming Sun; Ziquan Yu (World Journal of Microbiology and Biotechnology, 2015)

A new antioxidant flavone glycoside from Scutellaria baicalensis Georgi - Meng-Hua Wang; Lin-Zhen Li; Jian-Bo Sun; Fei-Hua Wu; Jing-Yu Liang (Natural Product Research, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Collection and evaluation of Primula species of western Sichuan in China - Yin Jia; Jing-Long Zhao; Yuan-Zhi Pan; Ying Xu; Ling-Xia Sun; Qing-Lin Liu (Genetic Resources and Crop Evolution, 2014)

Flavonoids and other constituents from Aletris spicata and their chemotaxonomic significance - Lin-Zhen Li; Meng-Hua Wang; Jian-Bo Sun; Jing-Yu Liang (Natural Product Research, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

BODIPY Fluorescent Chemosensor for Cu2+ Detection and Its Applications in Living Cells: Fast Response and High Sensitivity - Li Quan; Tingting Sun; Wenhai Lin; Xingang Guan; Min Zheng; Zhigang Xie; Xiabin Jing (Journal of Fluorescence, 2014)

CD24 mediates gastric carcinogenesis and promotes gastric cancer progression via STAT3 activation - Ying-Chao Wang; Ji-Lin Wang; Xuan Kong; Tian-Tian Sun; Hao-Yan Chen; Jie Hong; Jing-Yuan Fang (Apoptosis, 2014)

A new indole alkaloidal glucoside from the aerial parts of Clematis terniflora DC. - Wen-Ting Li; Bing-Xian Yang; Wei Zhu; Ming-Hua Gong; Xiang-Dong Xu; Xiang-Hong Lu; Lian-Li Sun; Jing-Kui Tian; Lin Zhang (Natural Product Research, 2013)

IFNG polymorphisms are associated with tuberculosis in Han Chinese pediatric female population - Chen Shen; Wei-Wei Jiao; Wei-Xing Feng; Xi-Rong Wu; Jing Xiao; Qing Miao; Lin Sun; Bin-Bin Wang; Jing Wang; Fang Liu; Dan Shen; A-Dong Shen (Molecular Biology Reports, 2013)

New Evidence for the Role of Ethylene in Strawberry Fruit Ripening - Jing-Hua Sun; Jing-Jing Luo; Lin Tian; Chun-Li Li; Yu Xing; Yuan-Yue Shen (Journal of Plant Growth Regulation, 2013)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

Oxidative stress and MAPK involved into ATF2 expression in immortalized human urothelial cells treated by arsenic - Shengnan Liu; Fei Wang; Ling Yan; Lin Zhang; Yingli Song; Shuhua Xi; Jing Jia; Guifan Sun (Archives of Toxicology, 2013)

Adipogenic and osteogenic differentiation of Lin−CD271+Sca-1+ adipose-derived stem cells - Jingang Xiao; Xiaojuan Yang; Wei Jing; Weihua Guo; Qince Sun; Yunfeng Lin; Lei Liu; Wentong Meng; Weidong Tian (Molecular and Cellular Biochemistry, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

A new species of Carpinus (Betulaceae) from the Pliocene of Yunnan Province, China - Jing Dai; Bainian Sun; Sanping Xie; Zhicheng Lin; Jingyu Wu; Kequn Dao (Plant Systematics and Evolution, 2013)

Two new triterpenoid saponins from Caragana microphylla seeds - Cheng-Jian Zheng; Gui-Lin Jin; Jing-Ping Zou; Yi-Ping Jiang; Pei-Xin Sun; Lu-Ping Qin (Journal of Natural Medicines, 2013)

Paenibacillus beijingensis sp. nov., a novel nitrogen-fixing species isolated from jujube garden soil - Miao Gao; Lin-qi Xie; Ya-xiong Wang; Jian Chen; Jing Xu; Xiao-xia Zhang; Xin-hua Sui; Jun-lian Gao; Jian-guang Sun (Antonie van Leeuwenhoek, 2012)

The dissection and SSR mapping of a high-temperature adult-plant stripe rust resistance gene in American spring wheat cultivar Alturas - Lei Zhao; Jing Feng; Chun-Yu Zhang; Xiao-Dan Xu; Xian-Ming Chen; Quan Sun; Qing Miao; Shi-Chang Xu; Feng Lin (European Journal of Plant Pathology, 2012)

Is the Evolution of Viviparity Accompanied by a Relative Increase in Maternal Abdomen Size in Lizards? - Yan-Yan Sun; Yu Du; Jing Yang; Tian-Bao Fu; Chi-Xian Lin; Xiang Ji (Evolutionary Biology, 2012)

Microbial methane cycling in a terrestrial mud volcano in eastern Taiwan - Yung‐Hsin Chang; Ting‐Wen Cheng; Wen‐Jing Lai; Wen‐Yu Tsai; Chih‐Hsien Sun; Li‐Hung Lin; Pei‐Ling Wang (Environmental Microbiology, 2012)
Summary Microbial communities responsible for methane cycling in mud volcanoes onshore are poorly characterized. This study analysed bubbling fluids and cored sediments retrieved from a mud volcano in eastern Taiwan. The pore water profiles revealed that methane concentrations generally increased with depth and changed dramatically at different depth intervals at different sites. The methane concentrations were inversely correlated with Fe 2+ /Mn 2+ concentrations and δ 13 C values of methane, marking iron/manganese‐methane transition zones in the sediment cores. Archaeal communities were dominated by ANME‐2a members and methylotrophic methanogens, whereas bacterial communities consisted primarily of Proteobacteria, Firmicutes and Bacteroidetes . The 16S rRNA gene copy numbers of ANME‐2a and Desulfuromonas / Pelobacter populations varied by two to three orders of magnitude along the profile and exhibited a pattern comparable with those of Fe 2+ and δ 13 C values of methane. These lines of evidence suggest a coupling between anaerobic methanotrophy and metal reduction in the metal‐methane transition zones under sulfate‐deficient conditions, a metabolic scheme contrasting with that observed in marine cold seeps. Anaerobic methanotrophs proliferate by removing methane produced from in situ methanogenesis and originating from the deep source. Methane finally emitted into the atmosphere is quantitatively and isotopically altered by various microbial processes compartmentalized at different depth intervals.

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Over-expression of the Arabidopsis Na+/H+ antiporter gene in Populus deltoides CL × P. euramericana CL “NL895” enhances its salt tolerance - Guirong Qiao; Renying Zhuo; Mingying Liu; Jing Jiang; Haiying Li; Wenmin Qiu; Luanyin Pan; Sheng lin; Xiaoguo Zhang; Zongxiu Sun (Acta Physiologiae Plantarum, 2011)

Comparative expression analysis of dehydrins between two barley varieties, wild barley and Tibetan hulless barley associated with different stress resistance - Jun-Bo Du; Shu Yuan; Yang-Er Chen; Xin Sun; Zhong-Wei Zhang; Fei Xu; Ming Yuan; Jing Shang; Hong-Hui Lin (Acta Physiologiae Plantarum, 2011)

Overexpression of constitutively active BMP-receptor-IB in mouse skin causes an ichthyosis-vulgaris-like disease - Xueyan Yu; Ramón A. Espinoza-Lewis; Cheng Sun; Lisong Lin; Fenglei He; Wei Xiong; Jing Yang; Alun Wang; YiPing Chen (Cell and Tissue Research, 2010)

5-ketoreductase from Streptomyces bingchengensis: overexpression and preliminary characterization - Xiang-Jing Wang; Cheng-Qin Wang; Xiao-Lin Sun; Wen-Sheng Xiang (Biotechnology Letters, 2010)

Proteomic Analysis of Interactions Between the Generalist Herbivore Spodoptera exigua (Lepidoptera: Noctuidae) and Arabidopsis thaliana - Ju-Hong Zhang; Li-Wen Sun; Lin-Lin Liu; Jie Lian; Shao-Li An; Xu Wang; Jing Zhang; Jun-Ling Jin; Shan-Yu Li; Jing-Hui Xi (Plant Molecular Biology Reporter, 2010)

Study on the quantitative structure–toxicity relationships of benzoic acid derivatives in rats via oral LD50 - Ye-zhi Sun; Zuo-jing Li; Xin-li Yan; Lin Wang; Fan-hao Meng (Medicinal Chemistry Research, 2009)

Molecular cloning and recombinant expression of a gene encoding a fungal immunomodulatory protein from Ganoderma lucidum in Pichia pastoris - Jing-Wei Lin; Li-Xia Hao; Gui-Xue Xu; Fei Sun; Feng Gao; Ren Zhang; Li-Xia Liu (World Journal of Microbiology and Biotechnology, 2009)

Preliminary studies on the chemical characterization and antioxidant properties of acidic polysaccharides from Sargassum fusiforme - Jing Zhou; Nan Hu; Ya-lin Wu; Yuan-jiang Pan; Cui-rong Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

Impact of genetic polymorphisms of leptin and TNF-α on rosiglitazone response in Chinese patients with type 2 diabetes - Hai-Ling Liu; Yang-Gen Lin; Jing Wu; Hong Sun; Zhi-Cheng Gong; Ping-Cheng Hu; Ji-Ye Yin; Wei Zhang; Dan Wang; Hong-Hao Zhou; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2008)

A new cytotoxic cholesterol sulfate from marine sponge Halichondria rugosa - Hong-Jun Zhang; Jing-Bo Sun; Hou-Wen Lin; Zeng-Lei Wang; Hua Tang; Ping Cheng; Wan-Sheng Chen; Yang-Hua Yi (Natural Product Research, 2007)

Changes of Src-suppressed C kinase substrate expression in cytokine induced reactive C6 glioma cells - Lin-Lin Sun; Chun Cheng; Hai-Ou Liu; Feng Xiao; Jing Qin; Xiao-Yi Shao; Ai-Guo Shen (Neuroscience Bulletin, 2007)